2016
DOI: 10.1038/srep20023
|View full text |Cite
|
Sign up to set email alerts
|

Toward Contactless Biology: Acoustophoretic DNA Transfection

Abstract: Acoustophoresis revolutionized the field of container-less manipulation of liquids and solids by enabling mixing procedures which avoid contamination and loss of reagents due to the contact with the support. While its applications to chemistry and engineering are straightforward, additional developments are needed to obtain reliable biological protocols in a contactless environment. Here, we provide a first, fundamental step towards biological reactions in air by demonstrating the acoustophoretic DNA transfect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 40 publications
(50 reference statements)
0
36
0
1
Order By: Relevance
“…For instance, the frequency of SAWs vibrating at 100 MHz corresponds to a wavelength of less than 100 µm, making them desirable for higher resolution patterning. It has been shown that higher frequency acoustic waves can be used to precisely pattern cells and nanoparticles 287,293–297. Wu demonstrated the use of acoustic tweezers to trap latex microparticles and clusters of frog eggs in a potential well (regions of minimum potential energy) generated by two collimated, focused ultrasonic beams 298.…”
Section: Acoustic Patterningmentioning
confidence: 99%
“…For instance, the frequency of SAWs vibrating at 100 MHz corresponds to a wavelength of less than 100 µm, making them desirable for higher resolution patterning. It has been shown that higher frequency acoustic waves can be used to precisely pattern cells and nanoparticles 287,293–297. Wu demonstrated the use of acoustic tweezers to trap latex microparticles and clusters of frog eggs in a potential well (regions of minimum potential energy) generated by two collimated, focused ultrasonic beams 298.…”
Section: Acoustic Patterningmentioning
confidence: 99%
“…This probe, dubbed TubeCamp, comprises the calcium-sensitive derivative of GFP, GCamp3 11 , fused with the microtubule-binding domain of ensconsin (EMTB) 12 . GCamp fluorescence emission increases upon calcium binding 11 while fusions of EMTB with fluorescent proteins have been used in mammalian 13 , amphibian 14, 15 and invertebrate 14 cells to label microtubules. To determine whether TubeCamp reports on microtubule-proximal elevated [Ca 2+ ] i , TubeCamp and R-Geco, a calcium-sensitive reporter protein 16 were expressed in Xenopus oocytes which were then wounded to elicit a local [Ca 2+ ] i increase and microtubule reorganization 17 .…”
Section: Figurementioning
confidence: 99%
“…The acoustic levitation method (ALM) of sample manipulation [1][2][3][4][5][6] is of great importance and a promising candidate for potential mid-air lab-on-a-drop applications, including the solidification of materials 7 , chemical analysis 8,9 , X-ray crystallography 10 , DNA transfection 11 , blood analysis 12 , and microreactors 13 . ALM has been studied for the contactless handling of matter in air.…”
mentioning
confidence: 99%